FEATURES OF USE HEAT FOR SEWAGE SEWAGE PUMPING STATIONS - and and (Municipal economy of cities. Series: «Economy science», 2013)
We analyze the relationship between earnings of heat from waste water to the sewage pumping station premises during the cold season and mode of revenue sewage at the sewage pumping station. The effect of heat flow from wastewater to the possibility of reducing the load on the heating sewer pumping station.